Radio frequency cooking of pork hams followed with conventional steam cooking. (April 2020) - Muñoz, Israel; Serra, Xavier; Guàrdia, M. Dolors; Fartdinov, Dinar; Arnau, Jacint; Picouet, Pierre A.; Gou, Pere
Abstract: Radio frequency (RF) is a volumetric heating technology that reduces the time needed to cook foodstuffs, but heating is not evenly distributed. The aim of this work was to develop a two-step cooking process in a RF tunnel and in a steam oven (RF-ST) for pork hams and compare it to cooking in a steam oven (ST). The temperature distribution was monitored during cooking and the accumulated lethality was calculated. Cooking losses and physicochemical and sensory properties of the cooked product were analysed. Hot spots and overheating problems were identified during the RF cooking process and were reduced by shielding the ends of the hams with aluminium foil and by adjusting the times of both, RF and steam cooking. The total ST process time (360 min) was reduced by 50% in RF-ST (180 min). Hardly significant differences were observed in the technological and sensory quality of the final product. Regarding the food safety of the RF-ST process, the lowest accumulated lethality in RF-ST process was observed in the outer part of the hams, which can be increased by extending the ST processing time, obtaining a more evenly distributed accumulated lethality in comparison to the ST process. Highlights: Cooking time decreased by 50% using radio frequency in large calibre products. Best results obtained by combining radio frequency and steam cooking. Overheating problems minimized by shielding the product ends. Slight sensory quality differences observed between steam and RF-steam processes.